2011
DOI: 10.1371/journal.pone.0026811
|View full text |Cite
|
Sign up to set email alerts
|

Multiple doublesex-Related Genes Specify Critical Cell Fates in a C. elegans Male Neural Circuit

Abstract: BackgroundIn most animal species, males and females exhibit differences in behavior and morphology that relate to their respective roles in reproduction. DM (Doublesex/MAB-3) domain transcription factors are phylogenetically conserved regulators of sexual development. They are thought to establish sexual traits by sex-specifically modifying the activity of general developmental programs. However, there are few examples where the details of these interactions are known, particularly in the nervous system.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 78 publications
2
26
0
Order By: Relevance
“…To specify ray identities, DBL-1 pathway signaling regulates the expression of two transcription factors. DBL-1 pathway activity establishes dopaminergic fates in the A neurons of rays 5, 7, and 9 by blocking the activity of DMD-3/ DM (Doublesex/MAB-3) domain transcription factor (Siehr et al, 2011). DBL-1 pathway signaling is required for the expression of ceh-13 / labial Hox family transcription factor in the Bγ rectal blast cell lineage and ray complexes 5, 7, and 9, though males lacking ceh-13 still have functional copulatory structures (Stoyanov et al, 2003).…”
Section: Dbl-1 Pathwaymentioning
confidence: 99%
“…To specify ray identities, DBL-1 pathway signaling regulates the expression of two transcription factors. DBL-1 pathway activity establishes dopaminergic fates in the A neurons of rays 5, 7, and 9 by blocking the activity of DMD-3/ DM (Doublesex/MAB-3) domain transcription factor (Siehr et al, 2011). DBL-1 pathway signaling is required for the expression of ceh-13 / labial Hox family transcription factor in the Bγ rectal blast cell lineage and ray complexes 5, 7, and 9, though males lacking ceh-13 still have functional copulatory structures (Stoyanov et al, 2003).…”
Section: Dbl-1 Pathwaymentioning
confidence: 99%
“…Later studies showed that mab-3, which represses the transcription of genes related to the production of yolk proteins [25], is required for transcription of male-specific genes in sensory neurons of the head and tail [26][27][28] and is necessary for male-specific muscle differentiation [29]. Behavioral assays showed that male mab-3 mutants present deficits in attraction to and interaction with hermaphrodites [27].…”
Section: Caenorhabditis Elegansmentioning
confidence: 99%
“…Male mab-23 mutants have morphological abnormalities in their tails, gonads and nervous system, and are unable to sire progeny. In males, mab-23 has been implicated in the patterning of the nervous system [28,29], the development of male-specific muscles [28,29] and the development of ''+'' and ''++'': low and high level of expression respectively; ''-'': no expression detected; NP: not performed.…”
Section: Caenorhabditis Elegansmentioning
confidence: 99%
See 2 more Smart Citations